Tatacara Pemeriksaan Permohonan Dispensasi Kawin Menurut Perma Nomor 5 Tahun 2019 (Analisis Putusan No.0017/Pdt.P/2020/Pa.Lpk) - Muhammad Syukri Albani Nasution; Ali Akbar; Maimunah Siagian (AL-HUKAMA, 2020)
Children have the right to choose, whether to marry or not, and when their choice falls to marry, then the biggest thing to be considered is the age, the age that is considered safe and permissible for marriage, from a health perspective, from a psychological perspective, as well as from an economic standpoint. This study aims to see how the judges consideration in deciding marriage dispensation cases, based on the analysis of the judge's decision No.0017 / Pdt.P / 2020 / PA.Lpk. The method used in this research is normative juridical. Indonesia as a State party to the Convention on the rights of the child (Convention on the rights of children) assert, that all actions concerning children undertaken by institutions, social welfare institutions, state or private, courts, administrative authorities or legislative bodies, are implemented in the best interest of the child, to provide protection for children who choose to marry while they are hindered by age